The Relationship between Premium Collection and Investment of Insurance Companies: A Case Study of Prabhu Insurance Company - Yadav, Mukesh Kumar (Chaturbhujeshwar Academic Journal, 2024)
This study explores the influences of globalization on secondary social studies textbooks. It uses a qualitative case study method to explore how global topics like multiculturalism, environmental sustainability, and human rights are included in textbooks, teaching materials, and methods. The researchers collected data through interviews with two teachers and by analyzing documents to understand how global ideas are shown in textbooks. The findings indicate that globalization has improved the curriculum by promoting global citizenship and increasing awareness of different cultures. However, there are challenges, such as the risk of losing local culture and content. Balancing global themes with local contexts is essential to help students understand their diverse environment. The study also examines key topics in textbooks, showing how Social Studies help students understand social issues and build national identity. It emphasizes the importance of active participation in communities and how modern teaching methods can make Social Studies more engaging. Lastly, the research highlights how globalization encourages students to think critically about global challenges and their local effects.